Supply Chain Collaboration and their Impact on Firm Performance: An Empirical Study - Hally Hanafiah; Prijono Tjiptoherijanto; Anton Wachidin Widjaja; Setyo Hari Wijanto (International Journal of Supply Chain Management, 2019)
The purpose of this paper is to conceptualize the dimensions of supply chain management practices and their impact on firm performances. In this empirical paper, business competitiveness of the service provider’s logistics companies comprises facets relating to quality and delivery of their products to the customers. Besides, as far as faster product delivery to the customers is concerned, this can be ascribed to the extensive sales and distribution networks established by the top twenty service provider’s logistics companies in Indonesia. The methodology of this study depends on the Meta-analysis, whereby the results reveal a positive effect of supply chain management practices, as viewed by the respondents of the service provider’s logistics companies on business performance. Such positive effects of supply chain management practices on both business competitiveness and customer satisfaction are validated by prior studies as well, who observe that when activities are performed in sync with both suppliers and customers, it would significantly leverage firm business competencies as well as customer satisfaction. This also finds the echo in the study arguing that a long-term collaborative relationship with suppliers facilitate in garnering positive results in an array of activities as reflected in superior product quality, diminished length of lead time, prompt customer service.